See you later escalator! : mall math. - Time-Life for Children (Firm) (Alexandria, Va. : Time-Life for Children, 1993)
Stories, poems, riddles, games, and hands-on activities introduce early math skills, focusing on the mathematics one might encounter on a trip to the shopping mall.
Science Books & Films (A.A.A.S.).
4.1
K-3
Keywords: Mathematics -- Juvenile literature; Mathematics; Mathematical recreations; Mathematics; Mathematical recreations; Mathematics; Mathematical recreations